Kids, wait till you hear this! : my memoir - Minnelli, Liza; Feinstein, Michael; Getlin, Josh; Evans, Heidi (Grand Central Publishing, 2026)
"Global icon Liza Minnelli shares her inspiring story: stepping out from the long shadow of a mega-star mother and legendary film director father, fighting a lifetime battle with Substance Abuse Disorder, and emerging from it all to become a once-in-a-lifetime artist. Kids, Wait Till You Hear This! is the autobiography of EGOT icon Liza Minnelli. This fascinating, untold story reveals the intimate truth of the only child born to Hollywood legends Vincente Minnelli and Judy Garland. For the first time, here is Liza up close: raw, strong, sexy, hilarious and heartbreaking. Liza decided at the age of 16 that "sympathy is my mother's business. I give people joy." That veil of joy, however, masks a lifelong struggle with Substance Use Disorder ("SUD," which Liza inherited from her mother's branch of her family), boundless love to give and an equal need to receive it, broken marriages, multiple miscarriages, and hospitalizations--the highs and lows of unparalleled artistic success and lifelong friendships, as well as chronic anxiety and the threat of financial ruin. Despite every challenge, Liza's is a life wrapped in laughter and her tremendous capacity to give and receive love. Today at nearly 80, she opens her heart, mind and memories, sharing secrets we never knew. Liza's book celebrates supreme artistry and, more importantly, her human rights activism. "It's time to tell the truth," Liza says, "and help people heal, as I have, one day at a time.""--